Legal Entity State Universities Don't Have the Authority as Goods or Services Providers in the Perspective of Sharia Economic Law - Sumadi, Hendy (Universitas Muhammadiyah Surakarta, 2024)
The realization of cooperation ties between Legal Entity State Universities (PTN BH) and work partners, in practice, still has legal ties mechanisms that position PTN BH as goods/services providers. This research aims to determine the competence of PTN BH, which does not have a legal position as a goods/services provider in conducting legal ties with government and non-government partners. This renewable research was conducted to explore/understand PTN BH's competence in managing collaboration. In have rights practice, the realization of cooperation still shows that PTN BH is a provider of goods/services in carrying out cooperative relationships with Government and non-government partners. This research uses a normative doctrinal approach or normative juridical legal research, which examines the internal aspects of positive law or legislation. The data collection technique was carried out through a literature study in the form of secondary data in the form of articles that have been published in journals as basic research material. The results of this research show that there are basic principles for PTN BH in collaborating with partners, namely the non-profit principle, the tri dharma principle of higher education, and the principle of truth and justice from a Sharia perspective. Economic law following Sharia economic law principles.